2011
DOI: 10.1615/intjmedmushr.v13.i3.80
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Royal Sun Agaricus, Agaricus brasiliensis S. Wasser et al., Aqueous Extract in Mice Challenged with Salmonella enterica Serovar Typhimurium

Abstract: This study investigated the effects of Agaricus brasiliensis S. Wasser et al. (=Agaricus blazei Murrill sensu Heinem.) aqueous extract on small intestinal sIgA levels, serum TNF-alpha, IFN-gamma and IL-10 levels, splenic index, bacterial translocation, and histology of small intestine, spleen, and liver from mice orally challenged with 10(6) CFU of Salmonella enterica serovar Typhimurium (SEST). Splenic index values as well as sIgA, TNF-alpha, IFN-gamma, and IL-10 levels were not affected by either A. brasilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on its immunomodulatory effects, ABM was previously found to show protective activity against bacterial disease (Rumbaugh et al 2009, Coates et al 2002, CDC, 2013, Stojkovic et al 2014. Antimicrobial effects against Mycobacterium tuberculosis, M. bovis and Streptococcus pneumoniae had been related with the immune system (Coates et al 2002, Stojkovic et al 2014, but this was contradicted by the study of Fantuzzi et al (2011) who described that ABM extract did not promote immunostimulation and protection during experimental Salmonella enterica infection in 5 mice. The finding of Fantuzzi et al (2011) was a good reason for us to look for possible anti-QS properties of ABM extracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its immunomodulatory effects, ABM was previously found to show protective activity against bacterial disease (Rumbaugh et al 2009, Coates et al 2002, CDC, 2013, Stojkovic et al 2014. Antimicrobial effects against Mycobacterium tuberculosis, M. bovis and Streptococcus pneumoniae had been related with the immune system (Coates et al 2002, Stojkovic et al 2014, but this was contradicted by the study of Fantuzzi et al (2011) who described that ABM extract did not promote immunostimulation and protection during experimental Salmonella enterica infection in 5 mice. The finding of Fantuzzi et al (2011) was a good reason for us to look for possible anti-QS properties of ABM extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial effects against Mycobacterium tuberculosis, M. bovis and Streptococcus pneumoniae had been related with the immune system (Coates et al 2002, Stojkovic et al 2014, but this was contradicted by the study of Fantuzzi et al (2011) who described that ABM extract did not promote immunostimulation and protection during experimental Salmonella enterica infection in 5 mice. The finding of Fantuzzi et al (2011) was a good reason for us to look for possible anti-QS properties of ABM extracts. MIC's and MBC's of these extracts turned out equal to or better for inactivation of P. aeruginosa than those of ampicillin and streptomycin.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial effects of ABM such as against Mycobacterium tuberculosis , M. bovis and Streptococcus pneumoniae have been attributed to the immune system [5,7]. The preventive role of innate immunity was contradicted by the study of Fantuzzi et al [8] who showed that ABM extract did not promote immunostimulation and protection during experimental Salmonella enterica infection in mice.…”
Section: Introductionmentioning
confidence: 99%